Spontaneously Opening and Closing Macular Holes with Lamellar Hole Epiretinal Proliferation: A Longitudinal Optical Coherence Tomography Analysis - Omar Moussa; Jedrzej Golebka; Gabriel Gomide; Dvir Koenigstein; Hueyjong Shih; Royce W. S. Chen (Diagnostics)
Background/Objectives: Spontaneous macular hole closure is a rare phenomenon, with lamellar hole epiretinal proliferation (LHEP) frequently implicated as a potential mechanism. This study aims to analyze the presence of LHEP in patients with full-thickness macular holes (FTMHs) or lamellar macular holes (LMHs) that closed spontaneously without intervention. Methods: A retrospective longitudinal analysis of optical coherence tomography (OCT) scans was conducted for 73 patients diagnosed with FTMH or LMH in a single institution. Patients with documented spontaneous hole closure were further analyzed for the presence of LHEP, other OCT findings, and clinical characteristics. Results: Of the 73 patients, eight (11%) exhibited spontaneous closure of their macular holes. LHEP was identified in all cases, regardless of hole type (FTMH or LMH). Associated OCT features on diagnosis included VMT in one eye (13%), partial or complete posterior vitreous detachment in seven eyes (88%) and epiretinal membrane in eight eyes (100%). During hole closure, an outer nuclear layer bridge was noted in six eyes (75%). Various extents of outer retinal recovery were noted following closure. After closure, five holes (63%) remained closed without further intervention, while three (38%) reopened and required surgical intervention. Conclusions: Spontaneous macular hole closure is strongly associated with the presence of LHEP, highlighting its potential role in retinal repair mechanisms. While in most patients the spontaneous closure is permanent, surgical intervention may be necessary in cases of hole recurrence.